Are clinicians using routinely collected data to drive practice improvement? A cross-sectional survey. (6th October 2021) - Gawthorne, Julie; Fasugba, Oyebola; Levi, Chris; Mcinnes, Elizabeth; Ferguson, Caleb; Mcneil, John j; Cadilhac, Dominique a; Everett, Bronwyn; Fernandez, Ritin; Fry, Margaret; Goldsmith, Helen; Hickman, Louise; et al.
Abstract: Background: Clinical registry participation is a measure of healthcare quality. Limited knowledge exists on Australian hospitals' participation in clinical registries and whether this registry data informs quality improvement initiatives. Objective: To identify participation in clinical registries, determine if registry data inform quality improvement initiatives, and identify registry participation enablers and clinicians' educational needs to improve use of registry data to drive practice change. Methods: A self-administered survey was distributed to staff coordinating registries in seven hospitals in New South Wales, Australia. Eligible registries were international-, national- and state-based clinical, condition-/disease-specific and device/product registries. Results: Response rate was 70% (97/139). Sixty-two (64%) respondents contributed data to 46 eligible registries. Registry reports were most often received by nurses (61%) and infrequently by hospital executives (8.4%). Less than half used registry data 'always' or 'often' to influence practice improvement (48%) and care pathways (49%). Protected time for data collection (87%) and benchmarking (79%) were 'very likely' or 'likely' to promote continued participation. Over half 'strongly agreed' or 'agreed' that clinical practice improvement training (79%) and evidence–practice gap identification (77%) would optimize use of registry data. Conclusions: Registry data are generally only visible to local speciality units and not routinely used to inform quality improvement. Centralized on-going registry funding, accessible and transparent integrated information systems combined with data informed improvement science education could be first steps to promote quality data-driven clinical improvement initiatives.